Laterally positioned double flap with the connective tissue graft for coverage of denuded root surface: A case report - Awadhesh Kumar Singh; Preeti Kiran (Wolters Kluwer Medknow Publications, 2014)
Background: The laterally positioned flap has been shown to effectively treat gingival recession. The average percentage of root coverage obtained with laterally positioned flap was 68%. When full-thickness laterally positioned flap was combined with connective tissue graft, the average percentage of root coverage was 88%. The purpose of this case report was to evaluate percentage of root coverage by laterally positioned double flap with the connective tissue graft. Patients and Methods: A patient with Miller class III gingival recession of 9 mm was treated by laterally positioned double flap with the connective tissue graft. The connective tissue graft was obtained by "trap-door" technique. Result: At the end of twelve months 83% root coverage was successfully achieved. Conclusion: The laterally positioned double flap with the connective tissue graft can be used for treatment of gingival recession defect successfully.